Construct validity of critical thinking disposition test in biology - Jayanti Syahfitri; Harry Firman; Sri Redjeki; Siti Sriyati (JURNAL BIOEDUKATIKA, 2020)
This Research includes seven indicators of Critical Thinking Disposition (CTD), namely truth seeking, open mind, analicity, systematicity, self confidence, inquisitiveness, and maturity. The purpose of this study is to look at the construct validity tests of CTD in biology at Bengkulu State University. This study involved 206 respondents, those are biology education students from Bengkulu State University with a level of study (years 1, 2, 3 and 4). After being analyzed by a Confirmatory Factor Analysis (CFA), the result showed that CTD Test had suitable construct validity. This result is supported by the received value of Convergent Validity which includes factor loading values of more than 0.5, while the Composite Relibility (CR) and Average Extract Variance (AVE) values for the seven indicators of CTD in sequence are Truth Seeking (CR = 0.96, AVE = 0.74), Open Mind (CR = 0.95, AVE = 0.67), Analicity (CR = 0.95, AVE = 0.68), Sistematicity (CR = 0.96, AVE = 0.70), Self Confidence (CR = 0.96, AVE = 0.70), Inquisitiveness (CR = 0.98, AVE = 0.82) and Maturity (CR = 0.95, AVE = 0.66). From the results can be concluded that the construct validity and composite reliability obtained by the test is good.